ISSUES OF DETERMINING THE VALUE OF OBJECTS OF APPRAISAL WHEN OBTAINING BANK LOANS (American Journal of Business Management, Economics and Banking, 2023)
The article reveals the role of appraisal activity in market relations, describes the cases in which there is a need for real estate appraisal, and also analyzes the current state of mortgage lending in Uzbekistan.